Sosyal Mesaj İçeren Konularda Etkileşimli "Google Doodle". - BAL, Gamze; ALPASLAN, Tutku Dilem (Afyon Kocatepe University Journal of Social Sciences / Afyon Kocatepe Üniversitesi Sosyal Bilimler Dergisi, 2025)
This study aims to examine the historical process of the world-renowned search engine Google's Google Doodle studies from past to present, and the distribution of designs in terms of subjects and techniques over the years. The whole process from the beginning of the studies on the website (https://www.google.com/doodles) to from 2021 years was taken in the research. Designs have been gathered under a total of 10 topics including: "Birthday", "Special Days", "Independence Day", "National Days and Holidays", "International Games", "Celebrations", "Anniversary", "Social Message Topics", "Google Doodle Games", "Seasons and Sky Events". Google Doodle design techniques were divided into three groups still, animated and interactive. Interactive design techniques, on the other hand, were divided into four groups slide, video, click/drag and game. All Google Doodle designs created between 1998 and 2021 were examined in terms of subject and design techniques, and then tables were created in line with the data obtained. Of the Google Doodle design changes, the "Birthday" content is the most sustained, while the least designed is the "Social Message" content. In terms of Google Doodle design techniques, the fixed doodle technique was used most, while the least applied one was the interactive doodle design technique. The application study of this study was limited to the topic "21 September Alzheimer's Day".